2021
DOI: 10.2147/cmar.s316544
|View full text |Cite
|
Sign up to set email alerts
|

Role of Phenotypes of Circulating Tumor Cells in the Diagnosis and Treatment of Colorectal Cancer

Abstract: Objective To investigate the relationship between circulating tumor cells (CTCs) and their subpopulations and colorectal cancer (CRC). To explore the application of CTCs’ numbers and positive rates in the diagnosis and treatment of CRC, and to assess the effect of surgery on CTCs numbers and positivity. Methods We identified CTCs using the CanPatrol technique after enrollment. Peripheral blood samples were collected from 74 CRC patients before anti-tumor treatment. CTCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…In this study, CTCs value increased with the deepening of tumor invasion depth, distant organ metastasis, and the progression of TNM staging (P < 0.05), but was not correlated with lymph node metastasis (P > 0.05). This is consistent with the study of Zhong et al [10], which showed that CTCs can well predict the depth of colorectal cancer invasion, the possibility of metastasis formation in the distal organ, and tumor staging.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, CTCs value increased with the deepening of tumor invasion depth, distant organ metastasis, and the progression of TNM staging (P < 0.05), but was not correlated with lymph node metastasis (P > 0.05). This is consistent with the study of Zhong et al [10], which showed that CTCs can well predict the depth of colorectal cancer invasion, the possibility of metastasis formation in the distal organ, and tumor staging.…”
Section: Discussionsupporting
confidence: 92%
“…Recent work describes the merits of this method in the detection and real time monitoring of CRC, allowing repeated temporal sampling for detection at curable stages[ 24 - 26 ]. A study done by Zhong et al [ 27 ] found that mesenchymal cell marker vimentin (M-CTC) in liquid biopsy directly correlated with tumor size, tumor, node and metastasis stage and vascular invasion. Unfortunately, the cost of liquid biopsy[ 26 ] outweighs its feasibility as a screening method, warranting discovery of affordable techniques that serve the same purpose for SBA.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that tumor metastasis is more significantly associated with the presence of M-CTCs and CTMs than with other CTC subgroups [ 39 ]. Similarly, Yuchen Zhong et al demonstrated that M-CTCs were correlated with tumor size, T stage, TNM stage, vascular invasion, and CEA, and M-CTCs > 1 were discovered to be associated with worse DFS [ 40 ]. According to a publication-based meta-analysis published in 2018 that included 15 published investigations with a total of 3129 patients, the presence of CTCs was highly correlated with poor survival (OS: HR = 2.36, 95% CI: 1.87–2.97; P = 0.006) and aggressive disease progression (PFS: HR = 1.83, 95% CI: 1.42–2.36; P < 0.00001).…”
Section: Main Textmentioning
confidence: 99%